2015
DOI: 10.13045/acupunct.2015021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sophorae Radix Pharmacopuncture Therapy on the Chunchu(ST25) for DSS-induced Colitis in Rats

Abstract: Objectives : The purpose of this study is to investigate the effects of Sophorae radix pharmacopuncture(SRP) therapy on the Chunchu(ST25) on intestinal disease in rats with dextran sulfate sodium(DSS)-induced colitis. Methods : The experimental model of colitis was induced by an infection of DSS for fifteen days. After colitis was induced, SRP therapy was practiced on the Chunchu(ST25) once every three days for a total of five times. Afterward, colon length, damage to the colonic mucosa, complete blood count, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In the study of Yang et al [12], which applied the Sophorae Radix Pharmacopuncture Therapy to Chunchu (ST25), and the study of Lee et al [38], which applied the Hwangnyeonhaedoktang Pharmacopuncture to Chunchu (ST25), the changes in length and weight of the colon were significant, and it was judged that Chunchu (ST25) itself had a stimulating effect as well as the effect of the pharmacopuncture itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Yang et al [12], which applied the Sophorae Radix Pharmacopuncture Therapy to Chunchu (ST25), and the study of Lee et al [38], which applied the Hwangnyeonhaedoktang Pharmacopuncture to Chunchu (ST25), the changes in length and weight of the colon were significant, and it was judged that Chunchu (ST25) itself had a stimulating effect as well as the effect of the pharmacopuncture itself.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Korean medicine have been proceeded and reported by the method of Korean medicine, and studies using medicinal prescriptions such as Soyumjungjang-tang [5], Jiyutang [6], Hwangryunhaedoktang [7] and studies using prescription of single herb such as Auklandia Lappa [8], Mume Fructus [9], Orostachys japonicas [10]. On the other hand, there are only a handful of studies that have applied acupuncture and pharmacopuncture such as Five Transport Points of the Spleen Meridian [11], Sophorae Radix Pharmacopuncture [12].…”
Section: Introductionmentioning
confidence: 99%